Restructuring Know How and Collateral - Dorothea Schäfer (Kredit und Kapital, 2002)
A close relationship often involves lenders in workouts for their distressed clients. Since restructuring activities need special expertise, banks must have previously ac- cumulated restructuring know-how. We analyze the factors which induce banks to invest in restructuring know-how and explore the relationship between restructur- ing know-how and outside collateral. We find that banks are likely to accumulate restructuring know-how if they enjoy market power or finance a large project. Out- side collateralization and restructuring know-how are substitutes. Since restructuring know-how preserves the value of the bank's inside collateral, this result indicates that empirical studies on debt securization and financial contracting need to distinguish clearly between the two types of collateral.
Additional information: The final version has been published by Duncker & Humblot: Restructuring Know How and Collateral / Dorothea Schäfer. In: Kredit und Kapital 35 (2002), 4, p. 572-597
Keywords: 330; Kredit; Bank; Theorie